Potential antioxidant activity of Lactobacillus fermentum KF7 from virgin coconut oil products in Padang, West Sumatra, Indonesia - SUMARYATI SYUKUR; SAFRIZAYANTI SAFRIZAYANTI; SITI ZULAIHA; EPI SUPRIWARDI; AULIA FAHMI; KUNTUM KH NURFADILAH; ENDANG PURWATI (Society for Indonesian Biodiversity, 2022)
Abstract. Syukur S, Safrizayanti, Zulaiha S, Supriwardi E, Fahmi A, Nurfadilah KK, Purwati E. 2021. Potential antioxidant activity of Lactobacillus fermentum KF7 from virgin coconut oil products in Padang, West Sumatra, Indonesia. Biodiversitas 23: 1628-1634. The isolation and characterization of five commercial Virgin Coconut Oil (VCO) products circulating in the local market of Padang city were conducted. In this study, eighteen isolates of lactic acid bacteria (LAB) were isolated and characterized microscopically, and biochemically. VCO-LAB isolates were Gram-positive bacilli and cocci, catalase-negative, and homofermentative (except VD was heterofermentative). There were three isolates of VCO-LAB (VB.3, VD and VE.4) that could produce gamma-aminobutyric acid (GABA). The highest concentration of GABA (19.5 mg/mL) was produced by isolate VB.3 after 72 hours of incubation and the addition of 7% MSG. VB.3 isolate shows the highest antioxidant activity with the addition of Monosodium glutamate (MSG), 68.13% for 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) ABTS and 88.02%. In addition, GABA-producing VCO-LAB could be grown in media containing 0.2-1.0 mM hydrogen peroxide, with the lowest optical density value of 0.82 nm. The antioxidant activity of VCO-LAB was affected by the GABA produced and by secondary metabolites such as peptides and antioxidant enzymes (NADH-oxidase, superoxide dismutase, NADH peroxidase and non-heme catalase). The highest antioxidant production was obtained in isolate VB.3 or Lactobacillus fermentum KF7.